Covid-19 Pandemic and Voter Participation in The 2020 Elections in West Java - Siddha, Arlan; Nurdin, Iing (HK-Publishing, 2022)
AbstractThis study objectively looks at the implementation of the 2020 PILKADA during the Covid-19 pandemic, which has an impact on voter participation. Doubts about the level of voter participation were denied with the participation rate which tends to increase with a percentage increase of 76.09%. Voter participation in PILKADA is a concept of public interest in policies to participate in a political policy. This research was conducted in West Java because it saw West Java participants with high DPT by comparing voter participation in 8 regencies/cities that held simultaneous elections in 2015 and 2020.Keywords: Voter Participation, Covid-19, PILKADA Jawa BaratÂ AbstrakKajian ini secara objektif melihat pelaksanaan PILKADA 2020 di masa pandemi Covid-19 yang berdampak pada partisipasi pemilih. Keraguan terhadap tingkat partisipasi pemilih terbantahkan dengan tingkat partisipasi yang cenderung meningkat dengan persentase kenaikan sebesar 76,09%. Partisipasi pemilih dalam PILKADA merupakan konsep kepentingan publik dalam kebijakan untuk berpartisipasi dalam suatu kebijakan politik. Penelitian ini dilakukan di Jawa Barat karena melihat peserta Jawa Barat dengan DPT tinggi dengan membandingkan partisipasi pemilih di 8 kabupaten/kota yang menyelenggarakan pilkada serentak tahun 2015 dan 2020.Kata Kunci: Partisipasi Pemilih, Covid-19, PILKADA Jawa Barat